'There is Security from this Place' : Promoting the Safety and Economic Vitality of Port Moresby’s Local Markets - Craig, David; Porter, Doug (World Bank, Washington, DC, 2017)
This Policy Note presents an analysis of and recommendations on the ongoing renovations of neighborhood markets in Port Moresby, Papua New Guinea (PNG). It is part of a program of work under the Urban Safety and Security Technical Assistance Activity that began in the National Capital District, Port Moresby, in late 2014 and is currently continuing in Lae, PNG’s second-largest city.Neighborhood markets are crucial for the economic vitality, safety, and social life of urban settlements. They need to be safe and secure areas to buy and sell, especially as women have a dominant presence in marketplaces, both as vendors and buyers. But they also need to function efficiently as markets, providing market sellers and their families with a daily income and buyers with fresh, cheap, and abundant produce, and they need to generate revenue to meet operating and maintenance costs. Port Moresby’s markets are by definition sites of economic opportunity. Yet, though all have some leadership structure, many struggle to enforce the rules and to access the resources required for safe, secure, and efficient market business. The Policy Note draws conclusions and makes recommendations relevant to the challenges faced by market renovators, be they government leaders and administrative officials, donor partners, or local people on whom market renovations depend for success, for each of the three phases of market renovation.